Systematic analysis of the pectin methylesterase gene family in Nicotiana tabacum and reveal their multiple roles in plant development and abiotic stresses - Sun, Jinhao; Tian, Zhen; Li, Xiaoxu; Li, Shaopeng; Li, Zhiyuan; Wang, Jinling; Hu, Zongyu; Chen, Haiqing; Guo, Cun; Xie, Minmin; Xu, Ruyan (Frontiers in Plant Science, 2022)
The pectin methylesterases (PMEs) play multiple roles in regulating plant development and responses to various stresses. In our study, a total of 121 PME genes were identified in the tobacco genome, which were clustered into two groups based on phylogenetic analysis together with Arabidopsis members. The investigations of gene structure and conserved motif indicated that exon/intron and motif organizations were relatively conserved in each group. Additionally, several stress-related elements were identified in the promoter region of these genes. The survey of duplication events revealed that segmental duplications were critical to the expansion of the PME gene family in tobacco. The expression profiles analysis revealed that these genes were expressed in various tissues and could be induced by diverse abiotic stresses. Notably, NtPME029 and NtPME043, were identified as homologues with AtPME3 and AtPME31, respectively. Furthermore, NtPME029 was highly expressed in roots and the over-expression of the NtPME029 gene could promote the development of roots. While NtPME043 could be induced by salt and ABA treatments, and the over-expression of the NtPME043 gene could significantly enhance the salt-stress tolerance in tobacco. Overall, these findings may shed light on the biological and functional characterization of NtPME genes in tobacco.